Convergent discrete numerical solutions of strongly coupled mixed parabolic systems - Jódar L.,; Casabán M.C., (Utilitas Mathematica, 2003)
This paper deals with the construction of convergent discrete numerical solutions of strongly coupled parabolic partial differential systems. The proposed method is based on the application of a discrete separation of variables technique to the discretized problem and its further exact solution which avoids the solution of large algebraic systems.